Nation and social democracy in Galicia: PSG-PSdG - Emilio Grandío Seoane (Pasado y Memoria, 2018)
Gallicia’s ability –or inability to be assigned equivalent competences to those of the other two historical nationalities sanctioned by the 1978 Constitution was a key issue in the process of creating the State of the Autonomous Regions. The pressure of very relevant sectors of the large Galician parties against the reduction of said competences brought about the first great hindrance against what some might consider as the development of a federal system. In this respect, the transfer to the PSOE of leading individuals from the PSG –an organization integrated in the Federation of Socialist Parties, with a strong nationalist commitment, was crucial. They took over a PSOE that urgently needed leading personnel. They provoked a 'transition within the transition' in Galician socialism, restructuring a good part of its organizational scheme and, above all, a radical opposition to accepting –massive mobilizations included– a Statute considered 'second level'.